Community-driven success in equity crowd funding: A study of brand engagement in Bangladesh two-sided markets - Md. Al Sabahel ; Murshed Alam ; Shahadat Hossain; Sultan Mahmud; Md. Karimul Alam (Global Academy of Multidisciplinary Studies, 2025)
Purpose: The aim of this study is to explain how entrepreneurs can benefit from using a brand community (BC) within a two-sided market, especially when they face difficulties in getting financial support. The study focuses on how ideas from Bangladesh-based research can help us understand online financial services, mainly equity crowdfunding. Methods: This research was carried out in Bangladesh and used netnography and qualitative methods to study an equity crowdfunding platform (ECFP). Online observations, community interactions, and qualitative data were collected from users of the platform to understand how the brand community works and supports the system. Results: The study found that in a two-sided market, the brand community around an equity crowdfunding platform (BCB) provides much more than digital funding. Community members also offer skills, social support, personal and professional contacts, and networking opportunities. These non-financial contributions strengthen the whole platform and help both entrepreneurs and investors. Conclusion: The findings show that a brand community embedded within an equity crowdfunding platform functions as a strategic resource that reinforces digital financing, promotes cooperative interactions, and supports ecosystem sustainability for entrepreneurs, investors, and platform managers. Limitation: The study is limited to qualitative data from one country and one type of crowdfunding platform, which may not fully represent other regions or financial systems. Contribution: This study shows how traditional ideas about brand communities can be adapted for modern digital financial services. It contributes to research in marketing, entrepreneurship, and digital finance, and gives managers practical insights for improving investor loyalty and business development in two-sided markets, especially in Bangladesh.